2020
DOI: 10.1002/srin.202070021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prestrain and Tempering on the Residual Stress of Low‐Carbon Microalloyed Steel

Abstract: The evolution of residual stress during thermomechanical treatment and its underlying mechanism are investigated. Further, two new mechanisms, precipitation plasticity mechanism and precipitation induced creep mechanism, which have important effects on residual stress are proposed. By using the mechanism proposed in this article number http://doi.wiley.com/10.1002/srin.201900421 by Yazheng Liu and co‐worker, low temperature regulation of residual stress can be realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Zheng et al [8,9] studied the effect of prestrain and the loading aging on the microstructure evolution of 7075 aluminum alloy, and found that prestrain can inhibit the coarsening of carbide and enhance the relaxation effect of residual stress. The influence of the prestrain on the precipitation behavior of the second phase in the tempering process is also confirmed by other researchers [10,12] Therefore, the PST process is an important means to regulate the precipitation behavior of carbides during tempering [3,13]. To the best of our knowledge, the studies of microstructure evolution in the tempering process using PST methods mainly concentrate on aluminum alloys, while the studies involving high strength steel have not been reported.…”
Section: Introductionsupporting
confidence: 62%
“…Zheng et al [8,9] studied the effect of prestrain and the loading aging on the microstructure evolution of 7075 aluminum alloy, and found that prestrain can inhibit the coarsening of carbide and enhance the relaxation effect of residual stress. The influence of the prestrain on the precipitation behavior of the second phase in the tempering process is also confirmed by other researchers [10,12] Therefore, the PST process is an important means to regulate the precipitation behavior of carbides during tempering [3,13]. To the best of our knowledge, the studies of microstructure evolution in the tempering process using PST methods mainly concentrate on aluminum alloys, while the studies involving high strength steel have not been reported.…”
Section: Introductionsupporting
confidence: 62%